CO sensor based on Au-GO doped Co-ZnO nano composite material and preparation method thereof
By using AU-GO to mix the CO-Zno nano-composite material to prepare the CO sensor, the MEMS gas sensor in the existing technologies in the existing technology has poor selectivity, low sensitivity, and high detection limit when detecting low concentrations of CO gas, and achieves low detection limit. , High sensitivity and good selective CO sensor.
Patent Information
- Application Number
- CN202411224209.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-21
AI Technical Summary
The existing MEMS gas sensors have poor selectivity, low sensitivity and high detection limit when detecting low concentration CO gas in transformers, which cannot meet the needs of transformer fault diagnosis.
The AU-GO doped CO-Zno nano-composite material is used to prepare the CO sensor. The CO3O4 to Zno is introduced through the ZIF-67 and the high temperature 煅 burning process to form a heterogeneous knot of P-N and improves the performance of the material through doping AU-GO.
The detection limit of the CO sensor is low, high sensitivity, and good selectivity, and can effectively detect CO gas with low concentrations of transformers.
Smart Images

Figure CN119335019A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of CO sensors, and in particular relates to a CO sensor based on Au-GO doped Co-ZnO nanocomposite material and a preparation method thereof. Background Art
[0002] With the development of intelligence and informatization, gas sensors, as an important part of the sensor field, have a wide range of application needs in environmental monitoring, agricultural production, toxic and harmful gas detection, and portable medical equipment. In the field of power systems, as an important power equipment, power transformers play a key role in the stability and safety of the entire power system. The safety of power equipment is directly related to the rapid development of the national economy and the construction process of the national smart grid. Among all kinds of electrical equipment, transformers are the core equipment of substations, and their safe and reliable operation is of great significance to ensure the safety and stability of the power grid. Carbon monoxide (CO) is a typical transformer fault diagnosis gas. By detecting the CO content in the transformer, the aging degree or fault condition of the transformer can be effectively monitored. However, its concentration in the transformer is often very low, generally only at the sub-ppm level. Therefore, it is of great significance to achieve high-precision online monitoring of trace CO in complex environments.
[0003] At present, the instruments and equipment for monitoring the operating status of power equipment mainly include gas chromatographs, photoacoustic spectrometers and infrared spectrometers, which generally have problems such as large size, high power consumption, poor timeliness and complex operation. For example, although gas chromatography analysis can achieve accurate measurement of multi-component trace gases, it requires the help of advanced laboratory equipment to separate, identify and quantify multi-component gases, and its sensitivity is low, making it difficult to effectively detect some low-concentration fault characteristic gases. In addition, these devices mostly use offline monitoring methods and cannot monitor the components and content changes of the state gas in the transformer in real time, which brings inconvenience to practical applications. In recent years, with the development of micro-nano sensing technology, MEMS gas sensors with miniaturization, low power consumption, high sensitivity and low cost are being continuously explored and studied by researchers. They have been widely used in many fields such as industrial production, food safety, environmental monitoring, disease diagnosis, etc., and also provide new methods for high-reliability detection of power equipment state gas. However, the existing MEMS gas sensors mainly use metal oxides as gas-sensitive materials, which generally have problems such as poor selectivity, low sensitivity and high detection limit, and cannot meet the application requirements of transformer fault diagnosis. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0008] Zn(Ac)2·2H2O and ZIF-67 were dissolved in deionized water, and NH4HCO3 and Au-GO were added after stirring. Mixed solution I was obtained after vigorous stirring. Mixed solution I was subjected to thermal reaction in a reactor.
[0009] After the reaction is completed and cooled to room temperature, the precipitate is collected by centrifugation, washed, dried, and calcined at high temperature to obtain Au-GO doped Co-ZnO nanocomposite material;
[0010] The Au-GO doped Co-ZnO nanocomposite was dissolved in anhydrous ethanol and mixed by ultrasonic to obtain a mixed solution II, which was then drop-coated on the surface of a micro-hot plate to form a CO sensor based on the Au-GO doped Co-ZnO nanocomposite.
[0011] The ZIF-67 is obtained by ultrasonically mixing Co(NO3)2·6H2O and 2-methylimidazole and thermally drying, and the Au-GO is obtained by mixing Au nanoparticle colloid and GO dispersion liquid in a constant temperature water bath and thermally drying.
[0012] As a preferred embodiment of the method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to the present invention, the mass ratio of ZIF-67 to Au-GO in the mixed solution I is 3 to 5:1.
[0013] As a preferred embodiment of the method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to the present invention, in the mixed solution I, the mass ratio of Zn(Ac)2·2H2O to ZIF-67 is 20-25:1, and the mass ratio of NH4HCO3 to Au-GO is 60-70:1.
[0014] As a preferred embodiment of the method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material of the present invention, the amount of deionized water used in the mixed solution I is 2-4 ml per 1 mg of ZIF-67.
[0015] As a preferred solution of the method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material of the present invention, the reaction time of the thermal reaction is 5 to 7 hours and the reaction temperature is 110 to 130°C.
[0016] As a preferred scheme of the preparation method of the CO sensor based on Au-GO doped Co-ZnO nanocomposite material described in the present invention, the calcination temperature of the high-temperature calcination is 450-500°C, the calcination time is 1.5-2.5h, and the heating rate is 1-3°C / min.
[0017] As a preferred solution of the method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material of the present invention, the concentration of the Au-GO doped Co-ZnO nanocomposite material in the mixed solution II is 45-55 mg / ml.
[0018] As a preferred solution of the preparation method of the CO sensor based on Au-GO doped Co-ZnO nanocomposite material of the present invention, the preparation method of ZIF-67 comprises:
[0019] Co(NO3)2·6H2O and 2-methylimidazole were dissolved in methanol solution, ultrasonically mixed at 80-100W for 10-20min, and then allowed to stand at room temperature. After centrifugation, methanol washing, and vacuum heat drying at 60-80℃ for 10-14h, ZIF-67 nanopowder was obtained.
[0020] The molar ratio of Co(NO3)2·6H2O to 2-methylimidazole is 1:3-5, and the amount of methanol used per 1 mmol of 2-methylimidazole is 1.5-2.5 ml.
[0021] As a preferred embodiment of the method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material of the present invention, the method for preparing Au-GO comprises:
[0022] HAuCl4·3H2O is dissolved in deionized water to obtain a HAuCl4·3H2O solution with a concentration of 0.5-1.5 mmol / L, and refluxed for 10-20 min at 100-120° C. to obtain a reflux reaction solution;
[0023] C6H5Na3O7·2H2O is dissolved in deionized water to obtain a C6H5Na3O7·2H2O solution, which is then slowly added dropwise to the reflux reaction solution, and the reflux reaction is continued for 10 to 20 minutes. After the reaction is completed, the solution is cooled to room temperature to obtain Au nanoparticle colloid, wherein the mass ratio of C6H5Na3O7·2H2O to HAuCl4·3H2O is 7 to 8:1;
[0024] GO is dispersed in deionized water, and ultrasonicated at 60W to 90W for 1h to 2h to obtain a dissociated GO dispersion with a concentration of 0.5 to 1.5 mg / ml. Au nanoparticle colloid is added to the GO dispersion, and the reaction is stirred in a constant temperature water bath at 95 to 105°C for 22 to 26h. After the reaction is completed and the solution is cooled to room temperature, it is centrifuged, washed, vacuum-dried at 60 to 80°C overnight, and ground to obtain Au-GO powder, wherein the mass ratio of Au nanoparticle colloid to GO is 1.5 to 2.5:1.
[0025] Another object of the present invention is to provide a CO sensor based on Au-GO doped Co-ZnO nanocomposite material.
[0026] Beneficial effects of the present invention:
[0027] The present invention utilizes ZIF-67 to introduce Co3O4 into ZnO through a hydrolysis and high-temperature calcination process, thereby increasing the specific surface area of the material while forming a pn heterojunction, and further improving the detection performance of the material for preparing a CO sensor by improving GO agglomeration by doping a certain amount of Au-GO. The CO sensor prepared by using the Au-GO doped Co-ZnO nanocomposite material has the characteristics of low detection limit, high sensitivity and good selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 This is a flow chart of the preparation of a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to Example 1 of the present invention.
[0030] Figure 2 This is a dynamic response curve diagram of the CO sensor prepared in Example 1 of the present invention.
[0031] Figure 3 This is a graph showing the detection limit test results of the CO sensor prepared in Example 1 of the present invention.
[0032] Figure 4 This is a diagram showing the selectivity test results of the CO sensor prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0036] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art, including: Zn(Ac)2·2H2O: McLean, CAS No.: 5970-45-6, NH4HCO3: Shanghai Trial, Batch No.: 20201228, Co(NO3)2·6H2O: McLean, CAS No.: 10026-22-9, 2-methylimidazole: Thermo Fisher, CAS No.: 693-98-1, HAuCl4·3H2O: McLean, CAS No.: 16961-25-4, GO: McLean, CAS No.: 7782-42-5
[0037] The performance test method and test environment of the CO sensor in the present invention refer to GJB 8264-2014.
[0038] Example 1
[0039] Reference Figure 1 This embodiment provides a method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material, specifically:
[0040] 1) Synthesis of Au-GO:
[0041] 20 mg of HAuCl4·3H2O was uniformly dissolved in 50 mL of deionized water to obtain a 1 mmol / L solution, which was transferred to a flask and refluxed at 115 °C for 15 min;
[0042] 147 mg of C6H5Na3O7·2H2O was dissolved in 10 mL of deionized water and then slowly added to the refluxing solution. The solution was refluxed for 15 min. During this process, the color of the solution was observed to gradually change from gray to purple and finally to wine red. After the reflux, the solution was cooled to room temperature to obtain Au nanoparticle colloid.
[0043] GO was dispersed in deionized water, and ultrasonicated at 90W for 1h to obtain a dissociated GO dispersion with a concentration of 1mg / mL. Au nanoparticle colloid was added to the GO dispersion, and the mixture was rapidly stirred in a 95℃ constant temperature water bath for 24h. After the solution was cooled to room temperature, it was centrifuged at 15000rpm and washed several times with ethanol and deionized water. Finally, it was dried overnight in a 75℃ electric blast drying oven and fully ground in a mortar to obtain Au-GO black powder.
[0044] 2) Synthesis of ZIF-67:
[0045] Co(NO3)2·6H2O (3.75 mmol) and 2-methylimidazole (2-MIM, 15 mmol) were dissolved in methanol solution (30 mL) respectively, ultrasonically mixed at 90 W for 15 min, allowed to stand at room temperature for 24 h, and then centrifuged at 10000 rpm. The mixture was then washed three times with methanol, and the precipitate was transferred to a 70 °C vacuum drying oven and dried for 12 h to obtain purple ZIF-67 nanopowder.
[0046] 3) Synthesis of Au-GO / Co-ZnO;
[0047] 0.44 g zinc acetate dihydrate (Zn(Ac)2·2H2O) and 20 mg ZIF-67 were dissolved in 60 mL deionized water and stirred rapidly for 15 min. Then, 0.32 g ammonium bicarbonate (NH4HCO3) and 5 mg Au-GO powder were added to make the mass ratio of ZIF-67 to Au-GO 4:1. After vigorous stirring for 3 h, the solution was transferred to a stainless steel reactor with a volume of 100 mL and kept at 120 °C for 6 h.
[0048] After cooling to room temperature, the precipitate was collected by centrifugation at 4000 rpm and washed repeatedly with deionized water for 4 times. The precipitate was transferred to a 70°C drying oven and dried overnight. The prepared powder was collected and placed in a ceramic crucible, transferred to a muffle furnace and calcined at 500°C for 2h (heating rate of 2°C / min) to obtain Au-GO / Co-ZnO.
[0049] 4) Preparation of CO sensor;
[0050] The Au-GO / Co-ZnO material obtained in step 3) is mixed with anhydrous ethanol to form a 50 mg / ml solution, and after ultrasonic mixing, the solution is drop-coated on a micro-hot plate to prepare a CO sensor based on Au-GO doped Co-ZnO nanocomposite material.
[0051] The performance test of the CO sensor prepared in this embodiment was carried out, and the results are as follows: Figures 2 to 4 As shown, Figure 2 is the dynamic response curve of the CO sensor, Figure 3 The detection limit test result of CO sensor is: Figure 4 The selectivity test result of the CO sensor shows that, at an operating temperature of 260° C., the response value of the CO sensor prepared by the present invention to 50 ppm CO gas reaches 5.84, and it has an extremely low detection limit and good selectivity.
[0052] Comparative Example 1
[0053] This comparative example is used to compare the performance of the sensor prepared in Example 1 of the present invention with other ZnO-based sensors in the prior art. The results are shown in Table 1.
[0054] Table 1
[0055] Material Concentration / ppm response Detection limit / ppm source Au-GO / Co-ZnO 50 5.84 0.1 This application In-ZnO 50 4.8 0.25 [1] ZnONP 80 3.85 0.25 [2]
[0056] Note: [1]Hjiri M,Dhahri R,Omri K,et al.Effect of indium doping on ZnObased-gas sensor for CO[J].Materials science in semiconductor processing,2014,27:319-325.
[0057] [2]Hjiri M, Bahanan F, Aida MS, et al. High performance CO gas sensor based on ZnO nanoparticles[J]. Journal of Inorganic and Organometallic Polymers and Materials, 2020, 30: 4063-4071.
[0058] As can be seen from Table 1, the sensor prepared in the present application also has great advantages in gas sensing performance compared with other ZnO-based CO gas sensors, especially in reducing the detection limit of the gas sensor.
[0059] Comparative Example 2
[0060] The difference between this comparative example and Example 1 is that cobalt nitrate is directly mixed with zinc acetate dihydrate without using ZIF-67 for synthesis and introduction, and the remaining steps and processes are adaptively referred to Example 1 to obtain the CO sensor of this comparative example.
[0061] Comparative Example 3
[0062] The difference between this comparative example and Example 1 is that the Au nanoparticle colloid is not mixed with the GO dispersion to prepare a nanomaterial without GO, and the Au-GO added in step 3) is adjusted to be the Au nanoparticle colloid, and the remaining steps and processes are adaptively referred to Example 1 to obtain the CO sensor of this comparative example.
[0063] Comparative Example 4
[0064] The difference between this comparative example and Example 1 is that GO is not mixed with Au nanoparticle colloid to prepare Au-free nanomaterial, the Au-GO added in step 3) is adjusted to GO, and the remaining steps and processes are adaptively referred to Example 1 to obtain the CO sensor of this comparative example.
[0065] The performance of the CO sensors prepared in Comparative Examples 2 to 4 was tested and compared with that in Example 1. The results are shown in Table 2.
[0066] Table 2
[0067] response Detection limit / ppm Example 1 5.84 0.1 Comparative Example 2 3.59 10 Comparative Example 3 4.12 0.3 Comparative Example 4 2.97 50
[0068] As can be seen from Table 2, the present invention uses ZIF-67 to introduce Co3O4 into ZnO through hydrolysis and high-temperature calcination processes, thereby increasing the specific surface area of the material while forming a pn heterojunction, and further improving the detection performance of the CO sensor for preparing the CO sensor by improving the agglomeration of GO by doping a certain amount of Au-GO. The CO sensor prepared by Au-GO doped Co-ZnO nanocomposite material has the characteristics of low detection limit, high sensitivity and good selectivity.
[0069] Example 2
[0070] The difference between this embodiment and embodiment 1 is that the mass ratio of ZIF-67 to Au-GO in step 3) is adjusted to 1:2, 2:1, 4:1, and 6:1, and the processes of the remaining steps are referred to embodiment 1 to obtain CO sensors with different mass ratios of ZIF-67 to Au-GO in this embodiment, and the relevant performance is tested. The results are shown in Table 3.
[0071] Table 3
[0072] ZIF-67: Au-GO response Detection limit / ppm 1:2 2.84 1.6 2:1 3.26 0.6 4:1 5.84 0.1 6:1 2.53 0.9
[0073] As can be seen from Table 3, the mass ratio of ZIF-67 to Au-GO in the present invention has a significant effect on the performance of the obtained CO. The analysis shows that ZIF-67 forms a pn heterojunction during the reaction. This structure helps to improve the charge separation efficiency and interfacial charge transfer capacity of the material. Adjusting the ratio of the two will affect the content of ZIF-67, thereby affecting the formation of the heterojunction. In addition, both ZIF-67 and Au-GO can increase the specific surface area of the composite material to a certain extent, providing more active sites for gas adsorption and detection. Although Au doping can improve the agglomeration of GO, too much Au-GO may cause itself to agglomerate, which reduces the dispersibility and specific surface area of the material, reduces the active sites, and thus reduces the performance of the sensor. In summary, changing the ratio of ZIF-67 and Au-GO may affect the performance of the material by affecting the pore structure, grain size, etc. inside the composite material. For example, changes in the pore structure may affect the diffusion and adsorption of the gas, and changes in the grain size may affect the electrical properties of the material.
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is that the high temperature calcination temperature in step 3) is adjusted to 400, 450, 500, 550, and 600° C., and the processes of the remaining steps are all referred to embodiment 1, and the CO sensors prepared at different calcination temperatures in this embodiment are obtained, and the relevant performance is tested. The results are shown in Table 4.
[0076] Table 4
[0077] Calcination temperature / ℃ response Detection limit / ppm 400 2.68 3.1 450 4.82 0.9 500 5.84 0.1 550 5.51 0.6 600 2.46 4.2
[0078] Example 4
[0079] The difference between this embodiment and embodiment 1 is that the heating rate of the high temperature calcination in step 3) is adjusted to 1, 2, 3, and 4°C / min, and the processes of the remaining steps are all referred to embodiment 1, to obtain CO sensors prepared at different calcination temperatures in this embodiment, and to test relevant performances. The results are shown in Table 5.
[0080] Table 5
[0081] Heating rate / ℃ / min response Detection limit / ppm 1 3.72 2.4 2 5.84 0.1 3 4.85 1.1 4 3.71 1.4
[0082] It can be seen from Tables 4 and 5 that the high-temperature calcination conditions of the Au-GO doped Co-ZnO nanocomposite material of the present invention also have a significant effect on the performance of the prepared CO sensor. This is because suitable calcination conditions are conducive to the complete crystallization and phase formation of the nanocomposite material, which can improve the stability and performance of the material. Too high or too low a temperature may lead to a decrease in specific surface area or collapse of the pore structure, thereby reducing the adsorption capacity and detection performance of the material.
[0083] In summary, the present invention discloses a CO sensor based on Au-GO doped Co-ZnO nanocomposite material and a preparation method thereof, wherein Co3O4 is introduced into ZnO by hydrolysis and high-temperature calcination of ZIF-67, thereby increasing the specific surface area of the material while forming a pn heterojunction, and further improving the detection performance of the CO sensor for preparing the CO sensor by improving GO agglomeration by doping a certain amount of Au-GO, and the CO sensor prepared by Au-GO doped Co-ZnO nanocomposite material has the characteristics of low detection limit, high sensitivity and good selectivity.
[0084] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material, characterized in that: include, Zn(Ac)2·2H2O and ZIF-67 were dissolved in deionized water, and NH4HCO3 and Au-GO were added after stirring. Mixed solution I was obtained after vigorous stirring. Mixed solution I was subjected to thermal reaction in a reactor. After the reaction is completed and cooled to room temperature, the precipitate is collected by centrifugation, washed, dried, and calcined at high temperature to obtain Au-GO doped Co-ZnO nanocomposite material; The Au-GO doped Co-ZnO nanocomposite was dissolved in anhydrous ethanol and mixed by ultrasonic to obtain a mixed solution II, which was then drop-coated on the surface of a micro-hot plate to form a CO sensor based on the Au-GO doped Co-ZnO nanocomposite. The ZIF-67 is obtained by ultrasonically mixing Co(NO3)2·6H2O and 2-methylimidazole and thermally drying, and the Au-GO is obtained by mixing Au nanoparticle colloid and GO dispersion liquid in a constant temperature water bath and thermally drying.
2. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 1, characterized in that: In the mixed solution I, the mass ratio of ZIF-67 to Au-GO is 3 to 5:
1.
3. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 2, characterized in that: In the mixed solution I, the mass ratio of Zn(Ac)2·2H2O to ZIF-67 is 20-25:1, and the mass ratio of NH4HCO3 to Au-GO is 60-70:
1.
4. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 3, characterized in that: In the mixed solution I, the amount of deionized water corresponding to 1 mg of ZIF-67 is 2 to 4 ml.
5. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 1, characterized in that: The reaction time of the thermal reaction is 5 to 7 hours, and the reaction temperature is 110 to 130°C.
6. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 1, characterized in that: The high-temperature calcination has a calcination temperature of 450-500° C., a calcination time of 1.5-2.5 hours, and a heating rate of 1-3° C. / min.
7. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 1, characterized in that: The concentration of the Au-GO doped Co-ZnO nanocomposite material in the mixed solution II is 45-55 mg / ml.
8. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 1, characterized in that: The preparation method of ZIF-67 comprises: Co(NO3)2·6H2O and 2-methylimidazole were dissolved in methanol solution, ultrasonically mixed at 80-100W for 10-20min, and then allowed to stand at room temperature. After centrifugation, methanol washing, and vacuum heat drying at 60-80℃ for 10-14h, ZIF-67 nanopowder was obtained. The molar ratio of Co(NO3)2·6H2O to 2-methylimidazole is 1:3-5, and the amount of methanol used per 1 mmol of 2-methylimidazole is 1.5-2.5 ml.
9. The method for preparing a CO sensor based on Au-GO doped Co-ZnO nanocomposite material according to claim 1, characterized in that: The preparation method of Au-GO comprises: HAuCl4·3H2O is dissolved in deionized water to obtain a HAuCl4·3H2O solution with a concentration of 0.5-1.5 mmol / L, and refluxed for 10-20 min at 100-120° C. to obtain a reflux reaction solution; C6H5Na3O7·2H2O is dissolved in deionized water to obtain a C6H5Na3O7·2H2O solution, which is then slowly added dropwise to the reflux reaction solution, and the reflux reaction is continued for 10 to 20 minutes. After the reaction is completed, the solution is cooled to room temperature to obtain Au nanoparticle colloid, wherein the mass ratio of C6H5Na3O7·2H2O to HAuCl4·3H2O is 7 to 8:1; GO is dispersed in deionized water, and ultrasonicated at 60W to 90W for 1h to 2h to obtain a dissociated GO dispersion with a concentration of 0.5 to 1.5 mg / ml. Au nanoparticle colloid is added to the GO dispersion, and the reaction is stirred in a constant temperature water bath at 95 to 105°C for 22 to 26h. After the reaction is completed and the solution is cooled to room temperature, it is centrifuged, washed, vacuum-dried at 60 to 80°C overnight, and ground to obtain Au-GO powder, wherein the mass ratio of Au nanoparticle colloid to GO is 1.5 to 2.5:
1.
10. A CO sensor based on Au-GO doped Co-ZnO nanocomposite material prepared by the preparation method according to any one of claims 1 to 9.